2002
DOI: 10.1074/jbc.m109064200
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-Phosphate, Present in Serum-derived Lipoproteins, Activates Matriptase

Abstract: We describe here a novel biological function of sphingosine 1-phosphate (S1P): the activation of a serine protease, matriptase. Matriptase is a type II integral membrane serine protease, expressed on the surface of a variety of epithelial cells; it may play an important role in tissue remodeling. We have previously reported that the activation of matriptase is regulated by serum. We have now identified the bioactive component from serum. First, the activity was observed to co-purify with lipoproteins by conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 40 publications
(19 reference statements)
2
78
0
Order By: Relevance
“…Consistent with this observation, no protein bands were detected using the activated matriptase-specific mAb (Fig. 1B, M69, lanes 1 and 3) (28,31). The inhibitor HAI-1 was detected in its uncomplexed form at 55 kDa, again consistent with the lack of active matriptase in these lysates (Fig.…”
Section: Exposure Of Epithelial and Carcinoma Cells To A Mildly Acidisupporting
confidence: 71%
See 1 more Smart Citation
“…Consistent with this observation, no protein bands were detected using the activated matriptase-specific mAb (Fig. 1B, M69, lanes 1 and 3) (28,31). The inhibitor HAI-1 was detected in its uncomplexed form at 55 kDa, again consistent with the lack of active matriptase in these lysates (Fig.…”
Section: Exposure Of Epithelial and Carcinoma Cells To A Mildly Acidisupporting
confidence: 71%
“…Activated matriptase was detected using the M69 mouse mAb, which recognizes an epitope present only on the activated form of the enzyme (28,31). Human HAI-1 was detected using the HAI-1-specific mouse mAb M19 (32).…”
Section: Methodsmentioning
confidence: 99%
“…Matriptase is a type II transmembrane serine protease (21) expressed as a single-chain form on epithelial cell types (5,22). It has been suggested that sphingosine 1-phosphate, a serumderived lipoprotein, is able to convert matriptase zymogen into its enzymatically active two chain form (23). In addition to HGFA and matriptase, there are a number of other serine proteases that, at least in vitro, convert pro-HGF into its active form.…”
mentioning
confidence: 99%
“…These observations suggest that matriptase could act as a cell surface activator to recruit and activate stromal-derived ECM-degrading proteases and motiUty factors. Furthermore, activation of matriptase in nontumorogenic human mammary epithelial cells (HMEC) seems to be tightly regulated by bioactive lipids, mainly sphingosine 1-phosphate (SIP) (3,4). Surprisingly, this SIP-based, physiological regulatory mechanism may be lost during breast cancer progression (5).…”
Section: Introductionmentioning
confidence: 99%